A GENE REGULATORY NETWORK MODEL FOR VERNALIZATION AND SEASONAL FLOWERING RESPONSE IN WINTER WHEAT AND BARLEY - I. L. Stepanenko; O. G. Smirnova; I. I. Titov (Вавиловский журнал генетики и селекции)
The transition from vegetative to reproductive development in wheat is regulated by seasonal cues, including vernalization and photoperiod. Here we present a simple logical model of the wheat development gene network. Vernalization accelerates flowering in winter cereals. It is regulated mainly by the vernalization genes VRN1, VRN2, and VRN3. After vernalization, VRN1 downregulates the VRN2 flowering repressor, thereby increasing the VRN3 level. The expression of VRN3 promotes further increases in the VRN1 transcription level, generating a positive feedback loop, which enhances VRN1 transcription to a threshold level required to initiate flowering. The products of the PPD1 and CO2 photoperiod genes increase VRN3 expression under long daylight conditions. Seasonal changes in day length are perceived by plant photoreceptors and transmitted to the circadian clock to modulate flowering time. Here we integrate data on vernalization and photoperiod genes in a gene network. Using a synchronous Boolean model, we have simulated the network dynamics. This model can be useful to test the coherence of experimental data and to hypothesize gene interactions that remain to be discovered.